Unraveling the aging-reversal potency of stem cell-derived extracellular vesicles in a rat model of premature cardiac senescence - Lidia Gómez-Cid; Alexia Campo-Fonseca; Mar Cervera-Negueruela; Alejandra Ocampo; Ángel Pinto; Juan Miguel Gil-Jaurena; Susana Suárez-Sancho; Francisco Fernández-Avilés; Lilian Grigorian-Shamagian (iScience)
Summary: Cardiosphere-derived cells (CDCs) and their extracellular vesicles (CDC-EVs) can rejuvenate and improve cardiac function, but their efficacy varies among donors. This study aimed to identify predictors of CDC-EV potency. CDCs from human donors were analyzed for phenotypical and biological properties. The anti-aging activity of CDC-EVs was tested using an in vitro matrix assay. Results showed that donor age did not determine potency, but CDC senescence correlated with most bioactive properties. However, senescence alone was insufficient to predict CDC-EV potency. CDC-EVs were classified as more potent (P-EVs) or less potent (NP-EVs) based on assay performance. In a rat model of premature cardiac aging, P-EVs reduced senescence-associated GLB1 gene expression and protected against hypertrophy and fibrosis, while NP-EVs had negative effects. The study concludes that CDC-EV anti-aging potency cannot be predicted by donor age or CDC senescence, proposing an in vitro potency assay for evaluating CDC-EVs before clinical use.